2021
DOI: 10.3390/cancers13071575
|View full text |Cite
|
Sign up to set email alerts
|

The Role of [18F]Fluciclovine PET/CT in the Characterization of High-Risk Primary Prostate Cancer: Comparison with [11C]Choline PET/CT and Histopathological Analysis

Abstract: The primary aim of the study was to evaluate the role of [18F]Fluciclovine PET/CT in the characterization of intra-prostatic lesions in high-risk primary PCa patients eligible for radical prostatectomy, in comparison with conventional [11C]Choline PET/CT and validated by prostatectomy pathologic examination. Secondary aims were to determine the performance of PET semi-quantitative parameters (SUVmax; target-to-background ratios [TBRs], using abdominal aorta, bone marrow and liver as backgrounds) for malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…[ 18 F]fluciclovine is a synthetic amino acid absorbed via the L-type amino acid transporter (LAT1) and the sodium-dependent neutral amino acid transporter (ASCT2), up-regulated in many human cancers, including PCa [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 F]fluciclovine is a synthetic amino acid absorbed via the L-type amino acid transporter (LAT1) and the sodium-dependent neutral amino acid transporter (ASCT2), up-regulated in many human cancers, including PCa [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of semiquantitative 18 F-FECh PET/CT parameters is controversial in initial PC staging. Zanoni et al showed a significant correlation between TBR and the International Society of Urological Pathology Score (derived from GS), using the liver as the reference organ [ 12 ]. These data are discrepant with our results, at least partially owing to the fact that we used the spleen as the reference organ.…”
Section: Discussionmentioning
confidence: 99%
“…Semiquantitative PET parameters were revealed to be useful for significantly discriminate malignant vs. non-malignant lesions [ 12 ]. Schaefferkotter et al showed that SUV could be a strong predictor of aggressive disease in the prostate (GS ≥ 4 + 3) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 27 Additional studies suggest that fluciclovine and [ 11 C]choline have similar sensitivity and specificity for the detection of the primary prostate cancer. 28 The most rigorous study evaluating the potential use of fluciclovine PET/CT for detection of primary prostate cancer was the FLUCIPRO trial, a prospective clinical trial which demonstrated a PET/CT sensitivity of 87% with a specificity of 56%. 29 A quantitative analysis of the findings of this study found that the maximum standardized uptake value (SUV max ) was significantly higher for those with clinically significant prostate cancer when compared with those with Gleason 3 + 3 = 6 prostate cancer.…”
Section: Pet/ct For Detection Of Localized Prostate Cancermentioning
confidence: 99%